Analisis Aktivitas Pemasaran Usaha Kecil dan Menengah Batik Besurek dengan Model Carson di Kota Bengkulu - Irdam, Amalia Rahayu; Anggarawati, Sularsih; Darmansyah (Universitas Brawijaya, Indonesia, 2014)
This research views that marketing activity level of Small Business Enterprise (SMEs) in Bengkulu. SMEs plays an important role in the development of the economy due to small businesses are provide of employment and create new jobs. The researcher tries to analyze marketing activity by examining the level of marketing from Carson's model. Based on this model, it will be answering the impact of business size and length of activity in small Medium Enterprise (SMEs). By using Carson's model will show the identification of activity and marketing level in SMEs. The activity consist of market knowledge, competitors, customers, marketing informations, significant events, competitive advantage prices, promotion, significant event prices, after sales services, product, distributions, positioning, and specific competitors. Due to the time and cost obstacle, this research only examines twenty SMEs of Batik Besurek in Bengkulu-Bengkulu Province. The Sample representatives are the SMEs in Bengkulu.